Diagnosing the Philippine economy toward inclusive growth - Canlas, Dante B.; Khan, Muhammad Ehsan; Zhuang, Juzhong; Asian Development Bank. (London Published for the Asian Development Bank by Anthem Press, 2009)
'Diagnosing the Philippine Economy' describes the conditions that depress economic growth in the Philippine economy and their causes and potential solutions.
A copublication of the Asian Development Bank and Anthem Press.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Economic development -- Philippines; Philippines -- Economic conditions